Strategi Penggunaan Sistem Informasi Dalam Komunikasi Bisnis Secara Elektronik - Zerimah Afgani Hasibuan; Nurbaiti (Jurnal Ekonomi dan Bisnis Digital, 2023)
Electronic commerce (eCommerce), broadly speaking, electronic commerce (e-Commerce) is defined as a way to sell and buy goods and services via the Internet network, but this of course includes various aspects. In the business world, information and communication technology is utilized for electronic trading or known as e-commerce. In e-commerce, parties carrying out trading activities only communicate through a public network, which in recent developments uses the internet. The aim of this research is how to use information systems in electronic business communications. Research method The research method used by the author in this research is qualitative research. It is hoped that the results of research, utilization and use of internet technology will provide great benefits to the competitive business world. Companies that are able to compete in this competition are companies that are able to implement technology into their companies.